PREDICTIVE ROLES OF SELF-EFFICACY AND EMOTIONAL INTELLIGENCE ON LEARNING MOTIVATION - Musfirah Musfirah; Imron Burhan (Universitas Labuhanbatu, 2026)
Purpose – This study aims to analyze the influence of self-efficacy and emotional intelligence on the learning motivation of elementary school students at SDIT Bina Insan, Parepare. The research is grounded in the recognition that psychological capacities, particularly self-efficacy and emotional intelligence, play a critical role in shaping students’ enthusiasm, persistence, and engagement in learning.Methodology – Employing a quantitative explanatory research design, the study involved sixth-grade students selected through purposive sampling. Data were collected from April to June 2025 using questionnaires, documentation, and interviews. Instrument validity was assessed using the Pearson product–moment correlation, and reliability using Cronbach’s alpha. The analysis included classical assumption tests, multiple linear regression, t-tests, and F-tests to determine both partial and simultaneous effects of the independent variables on learning motivation.Findings – The regression analysis produced the equation Y = 10.448 + 0.223X₁ + 0.527X₂, with an R value of 0.927 indicating a powerful relationship between the independent variables and learning motivation. The R² value of 0.860 shows that 86% of the variance in learning motivation is explained by self-efficacy and emotional intelligence. The t-test results confirmed that both self-efficacy (t = 2.835, p = 0.000) and emotional intelligence (t = 6.755, p < 0.001) have positive and significant effects, with emotional intelligence emerging as the dominant factor. The F-test (F = 86.095, p < 0.000) further demonstrated that the variables jointly exert a significant influence.Contribution – This study reinforces the theoretical and practical understanding that enhancing self-efficacy and emotional intelligence can substantially boost learning motivation in elementary school contexts, particularly within integrated Islamic education environments. The findings can inform the design of targeted psychopedagogical programs for teachers, parents, and policymakers to foster both cognitive and emotional readiness for learning.